Assessing exposure of semi-volatile organic compounds (SVOCs) in car cabins: Current understanding and future challenges in developing a standardized methodology. (December 2021) - Lexén, Jenny; Bernander, Maria; Cotgreave, Ian; Andersson, Patrik L.
Highlights: A review of semi-volatile organic compounds identified 64 studies from 2004 to 2021. A huge variation in sampling protocols was noted. Most reported data cover few chemical classes dominated by flame retardants. A meta -analysis indicated that SVOCs varied largely in air and especially in dust. A new sampling strategy aiming at reducing variability from sampling was suggested. Abstract: Semi-volatile organic compounds (SVOCs) can be found in air, dust and on surfaces in car cabins, leading to exposure to humans via dust ingestion, inhalation, and dermal contact. This review aims at describing current understanding concerning sampling, levels, and human exposure of SVOCs from car cabin environments. To date, several different methods are used to sample SVOCs in car cabin air and dust and there are no standard operating procedures for sampling SVOCs in cars detailed in the literature. The meta -analysis of SVOCs in car cabin air and dust shows that brominated flame retardants (BFRs) and organophosphate flame retardants (OPFRs) have been most frequently studied, primarily focusing on concentrations in dust. In dust, detected concentrations span over three to seven orders of magnitude, with highest median concentrations for OPFRs, followed by BFRs and, thereafter, polychlorinated biphenyls (PCBs). In air, the variation is smaller, spanning over one to three orders of magnitude, with phthalates and siloxanes having the highest median concentrations, followed by OPFRs, fluorotelomer alcohols (FTOHs) and BFRs. Assessments of human exposures to SVOCs in cars have, so far, mainly focused on external exposure, most often only studying one exposure route, primarily via dust ingestion. In order to perform relevant and complete assessments of human exposure to SVOCs in cars, we suggest broadening the scope to which SVOCs should be studied, promoting more comprehensive external exposure assessments that consider exposure via all relevant exposure routes and making comparisons of external and internal exposure, in order to understand the importance of in-car exposure as a source of SVOC exposure. We also suggest a new sampling approach that includes sampling of SVOCs in both car cabin air and dust, aiming to reduce variability in data due to differences in sampling techniques and protocols.